Exploring Key Determinants of Customer Satisfaction and Loyalty: Strategies for Business Sustainability in the Modern Era - Budi Hardjayanti, Nany; Andika Rifdayanti , Amirah; Bayu irawan, Satrya (International Journal of Management Science and Information Technology, 2025)
This study aims to explore the factors that influence customer satisfaction and loyalty as key elements for business sustainability in the modern era. The research employs a quantitative approach with a causal-explanatory survey design involving 200 respondents who are active customers of a company. The independent variables analyzed include product quality, price, customer service, innovation, and loyalty programs, with customer satisfaction and loyalty serving as the dependent variables. Data was analyzed using multiple linear regression to assess the impact of each independent variable on the dependent variables, alongside validity, reliability, and classical assumption tests to ensure model validity. The results show that all independent variables have a positive and significant effect on customer satisfaction and loyalty. Product quality is the most dominant factor (β = 0.46, p = 0.000), followed by customer service (β = 0.33, p = 0.000), innovation (β = 0.21, p = 0.001), loyalty programs (β = 0.18, p = 0.002), and price (β = 0.14, p = 0.007). Additionally, customer satisfaction was found to have a significant relationship with customer loyalty (β = 0.68, p = 0.000). These findings suggest that increasing satisfaction directly contributes to customer loyalty, which has implications for business sustainability. The study recommends that companies focus on improving product quality, innovation, customer service, and loyalty programs to enhance customer satisfaction and loyalty. Competitive pricing strategies should also be optimized to attract a broader market segment. In conclusion, understanding and managing these factors can support business sustainability in an increasingly competitive environment.